Remote teaching of philological specialisations in the light of experiences during the pandemic ‒ in the eyes of students and teachers - Widła, Halina (International Journal of Research in E-learning, 2022)
The article compares the results of the research conducted at the end of the winter semester 2019/2020 with the results from March 2021 as an extended teaching for the validity of extending the teaching offer for modern language studies by including innovative solutions using distance learning methods and techniques, with additional comments at the end of 2021. The opinions of 50 second-year students on the usefulness and effectiveness of IT innovations in lectures, seminars and practical language learning exercises were surveyed. The research showed that the pandemic situation verified students’ perceptions of the advantages and disadvantages of remote working. The data are also commented on by lecturers. It turns out that in all three types of classes, the opinions of students and staff range from moderately neutral at the beginning of 2020 towards teaching innovations, through more sceptical in March 2021 after the large-scale introduction of e-learning, to more favourable towards online innovations after a year of experience gained in 2021. Despite this general trend, there are considerable differences in the opinions of students and lecturers depending on the nature of the classes.